Atrazine Removal from Aqueous Solution by Biogenic Manganese Oxide and Persulfate: Kinetics and Removal Mechanism - Dogu, Nazlican; Tepe, Ozlem; Sahin, Mehmet (Springer Int Publ Ag, 2023)
New treatment methods based on biologically produced metal catalysts and reagents are being developed for the removal of pollutants. Biogenic manganese oxide (BMO) is one of the biogenic metal oxide types that have attracted attention especially in recent years. BMO is a suitable material for the removal of pollutants due to its notable activity and structural diversity. However, the role of biogenic manganese oxides in persulfate activation is so far unclear. In the present study, the biogenic manganese oxide was used as a catalyst in persulfate (PS) activation for the atrazine removal from aqueous solution. BMO/PS system was effective for removing the atrazine. The removal efficiency of the atrazine by BMO/PS system decreased with increasing pH. The removal efficiency increased with the increasing PS amount. Increasing the temperature facilitated the decomposition of the atrazine. It was revealed that 99.9% of the atrazine was removed in 300 min at pH 3 and 50 degrees C (Co: 5 mg/L, BMO: 2 g/L, PS: 1.4 g/L). In this system, the efficiency and stability of the catalyst decreased over three cycles. Sulfate and hydroxyl radicals were both involved in the atrazine removal. Based on the detected decay by-products, two degradation pathways have been proposed. The BMO were characterized via SEM-EDX, XRD, FTIR, and TGA techniques. This system reduced the environmental toxicity of atrazine. As a result, it has been revealed that this innovative material, BMO, has persulfate activation potential as an effective solution to the problem of persistent organic pollutants present in aquatic environments.
Keywords: Atrazine removal; BMO; Intermediate analysis; PS activation; Radical species